The Influence of Islamic Leadership and Islamic Organizational Culture on Employee Performance with Quality of Work Life as an Intervening Variable (A Study at PKU Muhammadiyah Hospital Yogyakarta) - Ardelia, Shafira; Mas'ud, Fuad (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
Hospitals play a very important role in the community, so they require human resources who have loyalty and are competent to be able to serve the community well according to procedures and optimal service which is expected to achieve organizational goals. This research aims to analyze and test the influence of Islamic leadership and Islamic organizational culture on employee performance with quality of work life as an intervening variable. This research used quantitative methods with 170 nurse respondents at PKU Muhammadiyah Hospital Yogyakarta. This research uses the SEM-PLS analysis technique which is carried out with the SmartPLS 3.0 application for data processing. The research results show that Islamic leadership, Islamic organizational culture, and quality of work life have a positive and significant effect on employee performance. Islamic organizational culture has a positive and significant effect on the quality of work life, while Islamic leadership does not affect the quality of work life. In addition, it was found that Islamic leadership did not affect employee performance through quality of work life, while Islamic organizational culture had a positive and significant effect on employee performance through quality of work life.